Perancangan User Experience menggunakan Perspective-Based Inspection pada Pengembangan SCRUM Situs Web PT.Nodeflux Indonesia - Kristina Lely Liana; Retno Indah Rokhmawati; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Nodeflux is an artificial intelligence company that has a core focus on developing computer vision technology. Nodeflux wants to redesign their website to be more informative, because more information is wanted to be given to users. The website must be able to clearly convey what the company has to offer, and user easily finding the information. In developing this website, Nodeflux using the agile development method. But, the agile method does not consider the UX aspect, this study aims to apply the UX aspect that is in line with the agile stage. This research using the Perspective-Based Inspection method, and using the UX Honeycomb as parameter. First step is a Small Up-Front Analysis (SUFA) to explore system needs, then create a conceptual design by dividing into three perspectives, namely ecology perspective, interaction perspective, and emotional perspective. Next, create a user story and make wireframe using the guidelines of the Department of Health and Human Services (HHS). The next stage is to the design of user experience stage, which starts with the stage of making hi-fi prototypes by providing colors that match with the company's brand. Then go to the sprint user experience stage, which is sprint planning, the results of which will be done by the developer. Then in the sprint review stage, testing is done by 2 participants using the Rapid Iterative Testing and Evaluation (RITE) method and the test results are evaluated by 3 experts using Perspective-Based Inspection. The results of the review will be taken to the sprint retrospective to enter the next sprint backlog. This was repeated until Sprint - IV was completed. After all the work is done, the final result is an improvement of the design of the Nodeflux company website. This study resulted in an increase in the value of user experience on usable, useful and findable values ​​obtained from the results of qualitative evaluations conducted by experts.